Urban Water Supply Sector Reform in Kathmandu Valley - Chapagain, Dol Prasad (Journal of the Institute of Engineering, 2014)
The sustainable governance of water resources requires that policy makers adapt to changing environmental and socioeconomic context. The efficient management of water resources is vital for its sustainable access and use. Therefore, adequate management practices are needed. Institutional reforms governing the water sector are undergoing remarkable changes and several efforts have been made in this direction for a long time to enhance the water service level. Currently, Kathmandu Upatyaka Khanepani limited (KUKL) is responsible for managing urban water and sanitation service to the Kathamndu Valley. It is the public company registered under the Nepal Government’s company Act 2006 and operates under public private partnership (PPP) modality, which is a part of urban water supply sector reforms of Kathamndu Valley. However, the basic requirement of water and sanitation service level has not changed sustainably. This paper focused to understand the institutional structure of the reforms and to examine the roles of institutions involved and stakeholders. This paper attempted to find out the real problem of water supply and why inadequate water service in Kathmandu valley though many institutional changes occurred. Literatures were reviewed and a descriptive, qualitative design was adopted to generate empirical data. This study finds that urban water supply sector reform of Kathmandu Valley is much closer to the Scott’s theory which consists of cognitive, normative and regulative structure and activities that work together provide stability and meaning to social behavior. However, findings are incongruent with this view point. Findings also show that focal problem of water supply is depleting water sources and widening the gap between demand and supply. Additionally, findings show that lack of coordination among stakeholders, weak institutional structure, unstable political scenario, and unplanned urbanization give rise to the problem, leading wider implications to the health of people and national economy. This paper discusses the results of the study and recommends improving the situation. DOI: http://dx.doi.org/10.3126/jie.v9i1.10678 Journal of the Institute of Engineering, Vol. 9, No. 1, pp. 130–141